2021
DOI: 10.1126/sciadv.abi4404
|View full text |Cite
|
Sign up to set email alerts
|

A dual-phase alloy with ultrahigh strength-ductility synergy over a wide temperature range

Abstract: High-entropy alloys (HEAs), as an emerging class of materials, have pointed a pathway in developing alloys with interesting property combinations. Although they are not exempted from the strength-ductility trade-off, they present a standing chance in overcoming this challenge. Here, we report results for a precipitation-strengthening strategy, by tuning composition to design a CoNiV-based face-centered cubic/B2 duplex HEA. This alloy sustains ultrahigh gigapascal-level tensile yield strengths and excellent duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Nutor et al discovered a CoNiV-based HEA strengthened by B2 nanoprecipitates through the addition of Al. 160 This alloy exhibited excellent tensile yield strength and ductility, particularly in cryogenic temperatures. The presence of twins and stacking faults near the nanoprecipitates accommodated the high interfacial stress between the FCC and B2 phases, effectively suppressing crack nucleation and prolonging strain hardening.…”
Section: Bulk Nanostructured Heasmentioning
confidence: 97%
“…Nutor et al discovered a CoNiV-based HEA strengthened by B2 nanoprecipitates through the addition of Al. 160 This alloy exhibited excellent tensile yield strength and ductility, particularly in cryogenic temperatures. The presence of twins and stacking faults near the nanoprecipitates accommodated the high interfacial stress between the FCC and B2 phases, effectively suppressing crack nucleation and prolonging strain hardening.…”
Section: Bulk Nanostructured Heasmentioning
confidence: 97%
“…In several fcc-structured HEAs, Al alloying has been a commonly exploited strategy to improve the room temperature yield strength and hardness [ 13 , 14 , 15 , 16 , 17 , 18 ]. Without exceeding the solid-solution limit of the fcc phase, the Al addition induces a solid-solution strengthening effect due to an elastic misfit caused by an enhanced lattice distortion [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on nanoparticle or cluster structures has confirmed the advantages of small catalysts ( 21 ). It is reasonable to expect that, given the above advantages of high-/medium-entropy alloys and amorphous alloys in the preparation of a new class of crystal (high-/medium-entropy)–glass nano-dual-phase alloys, the synergistic effects from the two phases may contribute to excellent HER performance as dual-phase material performs in mechanical property ( 22 ). Therefore, integrating the crystal-glass dual-phase ( 23 ) structure and size effect is an optimal approach to the fabrication of new-generation catalysts.…”
Section: Introductionmentioning
confidence: 99%